Association Between Serum IL-8 Concentrations and Severity of Knee Osteoarthritis: An Exploratory Cross-Sectional Study - Iskak, Iskak; Dewanta, Tunggul Bagus; Santoso, Anna Lewi; Aryanti, Novina; Syahzaqi, Idrus; Njoto, Ibrahim (Jambura Medical and Health Science Journal, 2026)
Introduction: Osteoarthritis (OA) is a chronic degenerative disorder of the joints that progresses over time, with inflammation playing a key role in its underlying mechanisms. Interleukin-8 (IL-8), a pro-inflammatory cytokine that participates in immune responses and neutrophil migration, has been associated with the process of cartilage breakdown in OA. This study was conducted to analyze the association between serum IL-8 concentrations and the radiographic severity of knee OA as exploratory evidence to enhance understanding of OA pathophysiology.Method: This exploratory observational research applied a cross-sectional approach in patients diagnosed with knee OA. Seven participants were enrolled through total sampling at the Larasati Pondok Osteoarthritis Elderly Health Center, Faculty of Medicine, Wijaya Kusuma University, Surabaya. Radiographic severity of OA was determined using the Kellgren–Lawrence grading system. Venous blood specimens were obtained to determine serum IL-8 concentrations as an indicator of systemic inflammation.Results: Statistical analysis demonstrated a significant inverse correlation between serum IL-8 concentrations and OA severity (r = −0.866, P = 0.012). These results indicate that IL-8 concentrations in serum are relatively elevated in the early phase of OA and tend to decline as the disease progresses.Conclusion: The findings of this exploratory study indicate that serum IL-8 may represent systemic inflammatory activity during the early stages of knee OA and holds potential as a biomarker candidate for future investigation. Further longitudinal studies involving larger sample sizes are necessary to validate its clinical relevance for OA detection and disease monitoring. Keywords: Cartilage, inflammation, interleukin-8, joint diseases, osteoarthritis, risk factors